Metadherin peptides containing CD4+ and CD8+ T cell epitopes as a therapeutic vaccine candidate against cancer. (23rd September 2016) - Dhiman, Gourav; Lohia, Neha; Jain, Sahil; Baranwal, Manoj
ABSTRACT: The concept of peptide‐based vaccines against cancer has made noteworthy progress. Metadherin (MTDH) overexpression and its role in the development of diverse cancers make it an attractive target for cancer immunotherapy. In the current study, six different T cell epitope prediction tools were run to identify MTDH peptides with multiple immunogenic regions. Further, molecular docking was performed to assess HLA‐peptide binding interactions. Nine and eleven peptides fragments containing multiple CD8 + and CD4 + T‐cell epitopes, ranging from 9 to 20 amino acids, respectively, were obtained using a consensus immunoinformatics approach. The three peptides that were finally identified as having overlapping CD4 + and CD8 + T‐ cell epitopes are ARLREMLSVGLGFLRTELG, FLLGYGWAAACAGAR, YIDDEWSGLNGLSSADP. These peptides were found to not only have multiple T cell epitopes but also to have binding affinity with wide HLA molecules. A molecular docking study revealed that the predicted immunogenic peptides (with single or multiple T cell epitopes) of MTDH have comparable binding energies with naturally bound peptides for both HLA classes I and II. Thus, these peptides have the potential to induce immune responses that could be considered for developing synthetic peptide vaccines against multiple cancers.